Social Criticism Da’wah Through Visual Works of @Terasdakwah During the COVID-19 Pandemic - Al Faiz, Farkhan; Akhmad Rifa'i (Kalijaga Journal of Communication, 2024)
This study aims to analyze the preaching message containing social criticism on the Instagram account @terasdakwah through a semiotic approach. The @terasdakwah account is a digital platform that actively spreads preaching content in a creative style relevant to current social issues. This descriptive qualitative study analyzes the meaning of the preaching message of social criticism (Tafriq) in a Visual Communication Design (VCD) work. The dissection of meaning in visual works uses the semiotic analysis knife of Sumbo Tinarbuko's visual communication and Roland Barthes' semiotic analysis. The results of this study show that: First, the connotative meaning revealed is that these visual works are a form of criticism of the government and society in general for the phenomena that occurred during the COVID-19 pandemic. The connotative level of meaning also found myths contained in the visual works studied, including the death of elderly Hajj pilgrims, the death of expertise, and prolonged frustration threatening mental health. Second, the message of social criticism (Tafriq) preaching contained in the three visual works uploaded by the Instagram account @terasdakwah is included in the first and second points in Alamsyah's theory. The first point is preaching as a correction for the reconstruction of social order, and the second point is preaching as an effort to institutionalize critical attitudes in Islamic society. Third, this study also shows that preaching is not only limited to religious rituals and formalities but can also be done by conveying social criticism. This research is hoped to provide scientific contributions to the study of preaching and communication science so that it can be a reference for further research on similar topics and discussions according to different contexts and objects of study.